Stereotactic Ablative Radiotherapy for Oligometastatic Disease in Liver - Kim, Myungsoo (Hindawi Publishing Corporation, 2014)
Liver metastasis in solid tumors, including colorectal cancer, is the most frequent and lethal complication. The development of systemic therapy has led to prolonged survival. However, in selected patients with a finite number of discrete lesions in liver, defined as oligometastatic state, additional local therapies such as surgical resection, radiofrequency ablation, cryotherapy, and radiotherapy can lead to permanent local disease control and improve survival. Among these, an advance in radiation therapy made it possible to deliver high dose radiation to the tumor more accurately, without impairing the liver function. In recent years, the introduction of stereotactic ablative radiotherapy (SABR) has offered even more intensive tumor dose escalation in a few fractions with reduced dose to the adjacent normal liver. Many studies have shown that SABR for oligometastases is effective and safe, with local control rates widely ranging from 50% to 100% at one or two years. And actuarial survival at one and two years has been reported ranging from 72% to 94% and from 30% to 62%, respectively, without severe toxicities. In this paper, we described the definition and technical aspects of SABR, clinical outcomes including efficacy and toxicity, and related parameters after SABR in liver oligometastases from colorectal cancer.